PENGGUNAAN METODE LEARNING STARTS WITH A QUESTION PADA MATA KULIAH BAHASA INGGRIS III UNTUK MENINGKATKAN PEMAHAMAN MEMBACA TEKS ARGUMENTASI - Fera Zasrianita (Manhaj: Jurnal Penelitian dan Pengabdian Masyarakat, 2016)
This research aimed to describe the use of Learning Starts with a Question method ‘Bahasa Inggris III’ subject to improve of reading comprehension in argumentation text onfourth students of Pendidikan Agama Islam program class D in Tarbiyah and Tadris faculty ofState Institute of Islamic Studies